Image-based clothes animation for virtual fitting - Zhou, Zhenglong; Shu, Bo; Zhuo, Zhaojie; Deng, Xiaoming; Tan, Ping; Lin, Steve (SA '12 SIGGRAPH Asia 2012 Technical Briefs, 2012)
We propose an image-based approach for virtual clothes fitting, in which a user moves freely in front of a virtual mirror (i.e., video screen) that displays the user wearing a superimposed virtual garment. The motions and deformations of the virtual garment are synthesized by tracking the user's skeleton and utilizing corresponding video clips of the actual garment worn by a model. Our system overcomes challenges in generating a convincing garment animation. With our technique, we developed a real-time system using a Microsoft Kinect camera that demonstrates effective clothes fitting results with a variety of garment types.